Your customer rules! : delivering the Me2B experiences that today's customers demand - Price, Bill, 1950- (Jossey-Bass, A Wiley Brand, 2015)
What you need to know about your customers Now more than ever, every interaction you have with customers is critical. Customers today have unlimited information at their fingertips'and can influence the purchase decisions and behaviors of millions of others. With this comes a shift in the balance of power, and every company must come to terms with the fact that the customer is in control. Interacting with customers in the way they want is an essential business strategy and in many industries, the key to business success. Executives still refer to B2B and B2C business models, as though companies control demand by going to customers with products and services. But as Bill Price and David Jaffe (authors of The Best Service is No Service) show, a new business model is emerging in which the customer directs the relationship. It is becoming a world of "Me2B"'one in which the customer, not the business, dictates the terms of engagement. In order for your business to thrive, you must create positive experiences to fulfill a range of customer needs. Though the mediums for customer engagement continuously evolve, Price and Jaffe show that customer needs remain unchanging. In Your Customer Rules!, they define a critical hierarchy of seven needs that your company can meet and apply as a methodology. Throughout this practical guidebook, Price and Jaffe share examples of companies who succeed by meeting these seven needs, including Amazon, Apple, IKEA, Nordstrom, USAA, Shoes of Prey, Vente-Privee, and Yamato Transport, as well as those that didn't. Your Customer Rules! offers tailored advice for companies at every stage, from nimble startups to legacy firms with established customer service practices'and everyone in between. With a simple, elegant solution for driving lasting value for customers, Your Customer Rules! is a clear guide for strengthening customer relationships and competing on more than price. It is essential reading for executives at all levels'business owners, marketing managers, and anyone who works directly with customers